Influence of Eimeria maxima coccidia infection on gut microbiome diversity and composition of the jejunum and cecum of indigenous chicken - Jebessa, Endashaw; Guo, Lijin; Chen, Xiaolan; Bello, Semiu Folaniyi; Cai, Bolin; Girma, Mekonnen; Hanotte, Olivier; Nie, Qinghua (Frontiers in Immunology, 2022)
Coccidiosis is an economically significant protozoan disease and an intracellular parasite that significantly impacts poultry production. The gastrointestinal tract microbiota plays a central role in host health and metabolism, and these microbes enhance chickens' immune systems and nutrient absorption. In this study, we analyzed the abundance and diversity of microbiota of the jejunum and cecum of a dual-purpose indigenous Horro chicken following Eimeria maxima infection. We compared microbial abundance, composition, and diversity at the 4- and 7- days post-infection using 16S rRNA gene sequencing. We obtained, on average, 147,742 and 132,986 high-quality sequences per sample for jejunum and cecum content, respectively. Firmicutes, Proteobacteria, Campilobacterota and Bacteroidota were the major microbial phylum detected in the jejunum content. Firmicutes were the dominant phylum for 4 -and 7-day jejunum control groups accounting for (>60% of the sequences). In the infected group Campilobacterota was the dominant phylum in the jejunum (> 24% of sequences) at 4-and 7-days post-infection groups, while Proteobacteria was predominant at 4- and 7-days post-infection of the cecum (> 40% of the sequences). The microbial genus Lactobacillus and Helicobacter were found in the jejunum, while Alistipes, Barnesiella and Faecalibacterium were detected in the cecum. In the jejunum, Helicobacter was dominant at 4 -and-7 days post-infection (≥24%), and Lactobacillus was dominant at 4 -and 7- days in the control group (> 50%). In 4- and 7-days post-infection, Alistipes genus was the more prevalent (> 38%) in the cecum. Thus, clear differences were observed in the bacterial microbiota distribution and abundance between the jejunum and cecum, as well as between infected and control groups for both tissues. The results indicate that chicken intestinal microbial imbalance (dysbiosis) is associated with Eimeria parasite infection and will likely affect the host-microbial non-pathogenic and pathogenic molecular interactions.